Ações públicas e privadas na conformação da cidade: estudo da dinâmica sócio-espacial de Limeria - SP, 1960-200 - Manfredini, Eduardo Alberto (2005)
The present study deals with the analysis and interpretation of changes that have occurred in the context of medium sized urbanizations in the state of São Paulo, specifically those that have been part physically and economically of the Administrative Region of Campinas, one of the areas that has shown dynamic processes of territorial and populational expansion, during the period of political, economical and social transformations in Brazil, taking as a time reference the period from 1960 to 2000. As a local reference, we have the Metropolitan Region of Campinas, considered to be the third largest industrial center in the country, right after the metropolitan areas of São Paulo and Rio de Janeiro. The city of Limeira was chosen as the central object of this study, a medium sized urbanization inserted in the regional context and influenced by the processes thereby derived which has shown a record of transformations connected to the expansion of urban networks and population growth in the last 40 years. The social-spatial dynamism of the city was analyzed here, observing the relations of the federal, state and regional economy with the conformation and configuration of the occupation of the spaces that are part of its urban tissue. In the same way, relations were observed between the increase of the city urban population and the issue of appropriation of urbanized land as an inducing element of spatial growth. Historical, economical and social happenings were also focused on in these interpretations, seeking to assess the expansion dynamism of the city along with the dividing up of the land, in this case as a forming element of the process and connected to regional formation. In relation to actions and agents that implemented the occupation of the city land, the performance of public authority and private initiative was observed in these scenarios, demonstrating some of the features of the way space is utilized in Limeira.